Consumer Perception Analysis of Samsung Products Related to the Controversial Issue of BTS's Suga as Brand Ambassador - Juwairiazizah Rasta; Nursantri Yanti; Juliana Nasution (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study analyzes consumer perceptions of Samsung products promoted by BTS's Suga as a brand ambassador, focusing on the impact of the controversial issue related to DUI involving Suga. The research method used is a descriptive qualitative approach with data collection through an open-ended questionnaire distributed online to Samsung consumers and BTS fans (ARMY). The collected data were analyzed using thematic analysis to identify dominant themes in consumer perceptions. The results of the study indicate that despite the controversial issue involving BTS's Suga as Samsung's brand ambassador, consumer perceptions of Samsung products have a positive view, although there are some weaknesses identified. Suga's influence as a brand ambassador is more pronounced among BTS fans, who feel an emotional connection with their idol. However, many respondents were not affected by the controversial issue and continued to judge the product based on its quality. Respondents also expect Samsung to handle this issue professionally and transparently. This study emphasizes the importance of managing controversial issues and selecting the right brand ambassador in marketing strategies to maintain brand loyalty and consumer purchasing decisions.